High-yield thermalized positronium at room temperature emitted by morphologically tuned nanochanneled silicon targets - Mariazzi, Sebastiano; Caravita, R.; Zimmer, Christian; Rienäcker, B.; Camper, A.; Belov, A.; Bonomi, G.; Brusa, R. S.; Castelli, F.; Consolati, G.; Doser, M.; Gjersdal, H.; et al. (Journal of physics. B, Atomic, molecular and optical physics, 2021)
Nanochanneled silicon targets with high positron/positronium (Ps) conversion rate and efficient Ps cooling were produced. Morphological parameters of the nanochannels, such as their diameter and length, were adjusted to get a large fraction of thermalized Ps at room temperature being emitted into vacuum. Ps cooling measurements were conducted combining single-shot positron annihilation lifetime spectroscopy and Doppler spectroscopy of the 13S → 23P transition. 2γ-3γ annihilation ratio measurements were also performed to estimate the positron/Ps conversion efficiency. In a converter with nanochannel diameter of 7-10 nm and depth of 3.89 μm, ∼28% of implanted positrons with an energy of 3.3 keV was found to be emitted as Ps with a transverse kinetic energy of 11 ± 2 meV. The reduction of the nanochannels depth to 1.13 μm, without changing the nanochannel diameter, was found to result in a less efficient cooling, highlighting the presence of Ps reflection from the bottom end of nanochannels.